The negative impact of illegal gold mining on the environmental sector in Batang Asai, Jambi - Try Susanti; Wiji Utami; Hidayat Hidayat (Center for Science and Technology, IAIN Surakarta, 2018)
The negative impact of Illegal Gold Mining / IGM on the environmental sector in Batang Asai District, Sarolangun Regency, Jambi was investigated through a descriptive qualitative method. The purpose of this study was to determine the negative impact of IGM activities to several ecosystems, the effect of IGM on community activities, and some efforts to reduce IGM. The instruments of data collection included observation, interviews, and documentation. Data were analysed through data reduction, data presentation, and conclusion withdrawal. The results showed that IGM activity had a negative impact on the environment namely noise pollution, dust, degradation on the quality of Batang Asai River, forest conversion, river siltation, the emergence of large holes, overburden, soil abrasion, the disappearance of Meranti plants (Shorea sp. ) and Damar (Agathis Damara). Besides that, other impacts were the declining population of Semah Fish (Tor sp.) which had become the special characteristic of fish in the area. Some efforts were made by the government to overcome and foster IGM activities, e.g. by providing counselling and sanctions in a judicial and non-judicial manner that was carried out continuously.